Fast-Track Zone: Analyzing Population and Throughput in an Emergency Department - Orbesen, Ditte; El-Faramawi, Mohamad; Sparke, Gitte; Christensen, Anne Friesgaard; Abrahamsen, Charlotte (Dansk Tidsskrift for Akutmedicin, 2025)
Introduction: Implementing a Fast-Track solution and optimizing processes for selected patient groups can significantly enhance throughput in an emergency department (ED). Due to limited knowledge about Fast-Track solutions in a Danish context, this study aimed to investigate the patient population and throughput in a newly established Fast-Track zone. Furthermore, the study aimed to investigate differences in patient- and admission-related characteristics among patients with medical conditions or abdominal symptoms. Methods: This prospective observational cohort study included all patients aged 16 years or older with low-acuity medical conditions or abdominal symptoms, who were referred to the ED and examined in the Fast-Track zone from September 1st, 2022, to April 30th, 2023. Data collection involved detailed recording of patient demographics, referral reasons, and Post-Fast-Track destinations, with validation by medical professionals to ensure accuracy. Results: During the study period, 2045 patients entered the Fast-Track zone, including 1301 with medical conditions and 744 with abdominal symptoms. Patients with medical conditions were significantly older (median age 62 vs. 49 years; p < 0.001) and more likely to be male (55% vs. 47%). Although their length of stay was shorter, they were more likely to revisit the Fast-Track zone compared to those with abdominal symptoms (50% vs. 20%). Ninety-three percent of the patients were discharged home the same day, some after treatment elsewhere, and some requiring follow-up, while 7% required admission. Conclusion: The Fast-Track zone for low-acuity medical conditions and abdominal symptoms has significantly streamlined throughput in the ED, allowing most patients to be discharged on the same day without extending the length of stay for the entire group of patients with medical conditions or abdominal symptoms. The Fast-Track criteria effectively differentiated patients with varying treatment needs. While one-third of contacts related to abdominal symptoms affected all age groups and genders equally, two-thirds involved older, predominantly male patients with various medical conditions and higher frequencies of ED visits.